2013
DOI: 10.1093/annonc/mds588
|View full text |Cite
|
Sign up to set email alerts
|

The need for accredited training in gynaecological oncology: a report from the European Network of Young Gynaecological Oncologists (ENYGO)

Abstract: Our data demonstrate the importance of accredited training and the need for harmonisation of gynaecological oncology training within Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…The European Society of Gynaecological Oncology has developed a structured training program with a detailed curriculum and competency-based logbook. 6 The need to ensure sufficiently skilled GO in the future is well documented. 2,3,11 This study represents an initial step in determining the role of an objective, nationally applied, summative technical skills assessment in the field of GO in Canada.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The European Society of Gynaecological Oncology has developed a structured training program with a detailed curriculum and competency-based logbook. 6 The need to ensure sufficiently skilled GO in the future is well documented. 2,3,11 This study represents an initial step in determining the role of an objective, nationally applied, summative technical skills assessment in the field of GO in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for urological and colorectal aspects of GO surgery. 6 Although there are numerous examples of low-cost, low-fidelity models to train and assess resident level surgical skill, 7Y11 it is unclear how these would appropriately differentiate between fellowship level candidates. 12,13 In an era of increasingly complex surgical procedures, it is timely and appropriate that our specialty consider the role of technical skills assessment of its trainees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13Y16 The European Network of Young Gynaecological Oncologists previously conducted a survey addressing trainee satisfaction with various areas of clinical and surgical training. 17 Interestingly, colorectal surgery was the single area with the lowest satisfaction of all, and they found that trainees in accredited training programs were significantly more likely to be satisfied with their colorectal surgery training (P = 0.003). The authors attributed this finding to better access to advanced debulking surgery and colorectal surgery at the accredited training sites.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, there have been calls for increased emphasis on surgical-skills training during the obstetric and gynecology residency period, 1 given the reduced operative exposure for these residents, compared to their predecessors. [1][2][3] There is concern that junior surgeons will not have the amount of experience required to acquire the advanced technical skills necessary for complex gynecologic oncology surgeries. Currently, operative case logs are used as a surrogate for assessing technical-skill experience.…”
Section: Introductionmentioning
confidence: 99%